Implementasi Aspek Gotong Royong pada Kurikulum Merdeka di TK Negeri 14 Bengkulu Selatan - Sriwanto, Windo; Suradi, Ahmad; Candra, Pasmah (UIN Fatmawati Sukarno Bengkulu, 2025)
The objectives of this research are 1) Analyze teachers' understanding regarding the implementation of mutual cooperation aspects in the independent curriculum at kindergarten states fourteen South Bengkulu, 2)Identifying forms of activities that involve aspects of mutual cooperation, and 3) Assessing the impact of implementing the mutual cooperation aspect on the social development and character of children. This study used a qualitative method with data collection techniques in the form of interviews, observation, and documentation. The results showed that teachers have a good understanding of the importance of mutual cooperation as a cultural value that must be instilled from an early age, and have implemented it through an age-appropriate approach. The mutual cooperation activities carried out included group games such as assembling puzzles, building block towers, ball relays, and community service inside and outside the classroom. The positive impact was seen in the increased attitudes of cooperation, helping each other, socialization, sharing, and empathy in children.